2021
DOI: 10.3389/fevo.2021.630990
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Research Landscape on Poaching: A Decadal Systematic Review

Abstract: Poaching is a widespread activity that affects wildlife management goals and undermines conservation efforts worldwide. Despite its complexity, poaching is still commonly addressed by researchers as a one-dimensional phenomenon. To deepen the scientific understanding of poaching, we conducted a systematic literature review in the Web of Science and Scopus databases for the last 10 years, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses methodology. We found that most studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 75 publications
0
0
0
Order By: Relevance
“…In this study, cultural needs/significance was the second most identified thematic driver of illegal hunting among local hunters. A recent global systematic review by Lavadinović et al [34] also identified socio-cultural influence as the third most prevalent identified driver of poaching. The corroborative findings of studies by Lavadinović et al [34] and this study suggest that cultural factors (values, beliefs and norms towards wildlife) may have profound effects on hunter's behaviour towards wildlife species and their habitats and on societal responses to illegal hunting [35,36].…”
Section: Proximate Underlying and Thematic Drivers Of Illegal Huntingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, cultural needs/significance was the second most identified thematic driver of illegal hunting among local hunters. A recent global systematic review by Lavadinović et al [34] also identified socio-cultural influence as the third most prevalent identified driver of poaching. The corroborative findings of studies by Lavadinović et al [34] and this study suggest that cultural factors (values, beliefs and norms towards wildlife) may have profound effects on hunter's behaviour towards wildlife species and their habitats and on societal responses to illegal hunting [35,36].…”
Section: Proximate Underlying and Thematic Drivers Of Illegal Huntingmentioning
confidence: 99%
“…A recent global systematic review by Lavadinović et al [34] also identified socio-cultural influence as the third most prevalent identified driver of poaching. The corroborative findings of studies by Lavadinović et al [34] and this study suggest that cultural factors (values, beliefs and norms towards wildlife) may have profound effects on hunter's behaviour towards wildlife species and their habitats and on societal responses to illegal hunting [35,36]. However, data on and understanding of socio-cultural values, beliefs and norms towards wildlife, bushmeat and the environment have been low [37].…”
Section: Proximate Underlying and Thematic Drivers Of Illegal Huntingmentioning
confidence: 99%
“…Like recent systematic review studies in green criminology with a mixture of the different online databases (Kurland et al 2017;Lavadinovic et al 2021;Mbzibain and Mohamed 2020;McFann and Pires 2020;Thomson et al 2019), this study used Scopus to collect data which is a citation index. Scopus is the largest abstract and citation database of peer-reviewed literature: scientific journals, books, and conference proceedings.…”
Section: Data Collectionmentioning
confidence: 99%
“…Local opinions about hunting can vary from it being a key livelihood activity to a very disapproved act, from a symbol of freedom to an expression of colonialism, having deep social and cultural roots. Hunting regulations are very different among countries, which classify different activities as poaching (Lavadinovićet al, 2021).…”
Section: Introductionmentioning
confidence: 99%